Cognitive-behavioral therapy in undergraduate psychology courses: A national mapping (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Cognitive-Behavioral Therapy (CBT) has been expanding in recent decades around the world. In Brazil, this psychological approach has also been expanding, but still with seeming restrictions related to undergraduate and post-graduate programs. Therefore, the objective of this study was to verify the number of undergraduate institutions that offer CBT courses. The sample assessed included 280 Brazilian psychology undergraduate programs. The websites of undergraduate programs in Psychology were assessed to obtain the respective curricular matrices. Our main findings were that an expressive part of the courses teach CBT, demonstrating that the approach has developed and is a part of the academic curriculum of several educational institutions. However, there are only a few institutions that offer CBT as an independent discipline in the psychology undergraduate programs, and in general it's commonly a topic taught in association with other academic themes.
Keywords: cognitive-behavioral therapy; undergraduate programs; Brazil